Amino acid variation at VP1-145 of enterovirus A71 determines the viral infectivity and receptor usage in a primary human intestinal model - Aknouch, Ikrame; García-Rodríguez, Inés; Giugliano, Francesca Paola; Calitz, Carlemi; Koen, Gerrit; van Eijk, Hetty; Johannessson, Nina; Rebers, Sjoerd; Brouwer, Lieke; Muncan, Vanesa; Stittelaar, Koert J.; Pajkrt, Dasja; et al. (Frontiers in Microbiology, 2023)
Enterovirus A71 (EV-A71) can elicit a wide variety of human diseases such as hand, foot, and mouth disease and severe or fatal neurological complications. It is not clearly understood what determines the virulence and fitness of EV-A71. It has been observed that amino acid changes in the receptor binding protein, VP1, resulting in viral binding to heparan sulfate proteoglycans (HSPGs) may be important for the ability of EV-A71 to infect neuronal tissue. In this study, we identified that the presence of glutamine, as opposed to glutamic acid, at VP1-145 is key for viral infection in a 2D human fetal intestinal model, consistent with previous findings in an airway organoid model. Moreover, pre-treatment of EV-A71 particles with low molecular weight heparin to block HSPG-binding significantly reduced infectivity of two clinical EV-A71 isolates and viral mutants carrying glutamine at VP1-145. Our data indicates that mutations in VP1 leading to HSPG-binding enhances viral replication in the human gut. These mutations resulting in increased production of viral particles at the primary replication site could lead to a higher risk of subsequent neuroinfection.